PERAN PROGRAM INSENTIF NON-FINANSIAL DALAM MENCIPTAKAN LINGKUNGAN KERJA YANG PRODUKTIF DI BANK BNI GUNUNGSITOLI - Gulo, Elman Syukur; Waruwu, Meiman Hidayat; Mendrofa, Syah Abadi; Lase, Heseziduhu (Jurnal EMT KITA, 2024)
This study aims to analyze the role of non-financial incentive programs in creating a productive work environment at PT Bank Negara Indonesia (Persero) Tbk Gunungsitoli Branch. The non-financial incentive programs at this company are designed to enhance employee motivation and job satisfaction through various non-material rewards, such as best employee awards, recognition certificates, and career development opportunities. The study employs a qualitative method with a descriptive approach. Data were collected through interviews with human resource managers (HRD) as key informants and several employees as supporting informants. The findings reveal that the non-financial incentive programs at Bank BNI Gunungsitoli Branch have a positive impact on employee motivation, productivity, and collaboration. However, challenges exist in the implementation of these programs, including the relevance of incentives for all departments and transparency in performance evaluation. Based on these findings, it is recommended that the company expand the scope of incentives to cover aspects of work-life balance and broader career development, as well as improve transparency in the performance evaluation and incentive distribution processes.